Validation of the instrument to measure the impact of management skills of human capital as a strategy for good operation of the administrative process of smes dedicated to wholesale commerce located in ciudad obregón sonora, mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
This research aim is to determine the relationship between management skills and the functioning of the administrative process of SMEs in Ciudad Obregon Sonora, Mexico. The Official Journal of the Federation (2013) in Mexico provides that companies have a great importance in economic development, 99% are SMEs and contribute to 52% of GDP, generating 70% of jobs, therefore a factor determining remain in market is the management skills where the authors Whetten and Cameron (2005) establish a model that classifies the management skills personal, interpersonal and group where directly affect the functioning of the business management process. For the methodology are applied 81 questionnaires with 34 items to try to explain the variables in the framework theoric developed with answers on Likert scale and through Cronbach's alpha reliability coefficient for administrative process as dependent variable and independent variable was calculated Stress domain,Troubleshooting, Motivation, Leadership and Innovation, where the analysis introduced two models, largely explaining the variability of the dependent variable, the study is limited only to the management skills of managers of SMEs because this sector has a great importance worldwide and the future lines of research for this study just take it in other regions.
Keywords: Management skills; human capital; management process; SMEs; measurement instrument